Comparison of closed-chest drainage with rib resection closed drainage for treatment of chronic tuberculous empyema - Fang, Yong; Xiao, Heping; Sha, Wei; Hu, Haili; You, Xiaofang (Journal of Thoracic Disease; Vol 10, No 1 (January 31, 2018): Journal of Thoracic Disease, 2017)
Background: This study aimed to compare the efficacy of closed-chest drainage with rib resection closed drainage of chronic tuberculous empyema. Methods: This retrospective study reviewed 86 patients with tuberculous empyema in Shanghai Pulmonary Hospital from August 2010 to November 2015. Among these included patients, 22 patients received closed-chest drainage, and 64 patients received rib resection closed drainage. Results: The results showed that after intercostal chest closed drain treatment, 2 (9.09%) patients were recovery, 13 (59.09%) patients had significantly curative effect, 6 (27.27%) patients had partly curative effect, and 1 (4.55%) patient had negative effect. After treatment of rib resection closed drainage, 9 (14.06%) patients were successfully recovery, 31 (48.44%) patients had significantly curative effect, 19 (29.69%) patients had partly curative effect, and 5 (7.81%) patients had negative effect. There was no significant difference in the curative effect (P>0.05), while the average catheterization time of rib resection closed drainage (130.05±13.12 days) was significant longer than that (126.14±36.84 days) in course of intercostal chest closed drain (P